Characteristics of Post-ICU and Post-COVID Recovery Clinics in 29 U.S. Health Systems. (9th March 2022) - Danesh, Valerie; Boehm, Leanne M.; Eaton, Tammy L.; Arroliga, Alejandro C.; Mayer, Kirby P.; Kesler, Shelli R.; Bakhru, Rita N.; Baram, Michael; Bellinghausen, Amy L.; Biehl, Michelle; Dangayach, Neha S.; Goldstein, Nir M.; et al.
Abstract : OBJECTIVES: The multifaceted long-term impairments resulting from critical illness and COVID-19 require interdisciplinary management approaches in the recovery phase of illness. Operational insights into the structure and process of recovery clinics (RCs) from heterogeneous health systems are needed. This study describes the structure and process characteristics of existing and newly implemented ICU-RCs and COVID-RCs in a subset of large health systems in the United States. DESIGN: Cross-sectional survey. SETTING: Thirty-nine RCs, representing a combined 156 hospitals within 29 health systems participated. PATIENTS: None. INTERVENTIONS: None. MEASUREMENT AND MAIN RESULTS: RC demographics, referral criteria, and operating characteristics were collected, including measures used to assess physical, psychologic, and cognitive recoveries. Thirty-nine RC surveys were completed (94% response rate). ICU-RC teams included physicians, pharmacists, social workers, physical therapists, and advanced practice providers. Funding sources for ICU-RCs included clinical billing ( n = 20, 77%), volunteer staff support ( n = 15, 58%), institutional staff/space support ( n = 13, 46%), and grant or foundation funding ( n = 3, 12%). Forty-six percent of RCs report patient visit durations of 1 hour or longer. ICU-RC teams reported use of validated scales to assess psychologic recovery (93%), physical recovery (89%), and cognitive recovery (86%) more often in standard visits compared with COVID-RC teams (psychologic, 54%; physical, 69%; and cognitive, 46%). CONCLUSIONS: Operating structures of RCs vary, though almost all describe modest capacity and reliance on volunteerism and discretionary institutional support. ICU- and COVID-RCs in the United States employ varied funding sources and endorse different assessment measures during visits to guide care coordination. Common features include integration of ICU clinicians, interdisciplinary approach, and focus on severe critical illness. The heterogeneity in RC structures and processes contributes to future research on the optimal structure and process to achieve the best postintensive care syndrome and postacute sequelae of COVID outcomes.